Estudio anatómico de la madera de Psidium sartorianum (Myrtaceae) y Cordia gerascanthus (Boraginaceae) - Rebollar, Silvia; Quintanar, Alejandra; Perez, Carmen de la Paz (Instituto de Ecología, A.C., 1994)
Macroscopic and microscopic anatomical features of the wood of Psidium sartorianum (Berg.) Ndzu. and Cordia gerascanthus L. are described. The samples were collected in tropical rain forests of Puerto Morelos, Municipio of Benito Juárez, Quintana Roo. Values of measurable elements, botanical descriptions of each species, and characteristics of the trees are reported, as also local uses and those mentioned in the literature. The results of these studies are discussed.